PROSPEK PERBANKAN SYARIAH DI INDONESIA: CERAH ATAU BURAM? - YULIANTI YULIANTI (Jurnal Dialog, 2017)
Indonesia is one of the Asian countries that has proved the existence of syariah bankings. However, more efforts are still needed to fix existing problems faced. Beginning in 1991, Indonesia developed an Islamic economic by ways of building a syariah banking. Syariah banking is a kind of bank that operates without the use of interes in its transactions. At first, people were not sure with the performance of syariah bankings, but when these banks could survive during the 1997 economic cirisis from severe collapse, people are now sure that syariah bankings are a good place to save their money. As shown in the statistics of the Indonesian central bank (BI), syariah bankings show significant progress almost every year.